A prospective study using image analysis to assess the efficacy of a topical treatment kit for mild onychomycosis. Issue 2 (17th December 2019) - Khammo, Nancy; Chesters, Dave; Goldstone, Lauren; Kennedy, Gayle; Buckley, Carolyn
Summary: Background: Onychomycosis is a fungal infection of the nails and is one of the most common dermatological infections worldwide. Infection occurs predominantly in the nails of the feet and if left untreated patients, particularly in at‐risk populations, can develop more serious complications, including pain, fissuring and secondary infections. Fungal infections are also contagious and may spread to other nails or to family members. Topical treatments can be effective for mild cases of the disease and typically have fewer contraindications. However, generation of robust efficacy data for topical therapies is often hindered by the difficulties associated with monitoring progression of mild onychomycosis using the conventional methods of mycological culture to obtain confirmation of podiatrist assessments. Objectives: The aim of this study was to demonstrate image analysis as an effective method to monitor progression of fungal nail infections. Methods: A novel digital image analysis technique was used to evaluate improvement in the visual signs of onychomycosis, when using a topical treatment kit for mild fungal nail infections in 60 participants over a 280‐day period. Results: Image analysis demonstrated a significant ( P  < .0001) reduction from baseline of the affected nail area throughout the study period, results which were also perceived by the subjects themselves. Use of the treatment kit also limited the deterioration of the infection and prevented transmission to other nails. Conclusions: Image analysis was established as a viable method to monitor the progression of fungal nail infections over long periods and demonstrate a clinical benefit following treatment.